THE ANALYSIS OF THE PUBLIC SENIOR HIGH SCHOOL (SMAN) ENGLISH TEACHERS` SELF EFFICACY IN KUANTAN SINGINGI DISTRICT ON THE USE OF ICT - Bonita Bestari; Hadriana Hadriana; Supriusman Supriusman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The objectives of this quantitative research are to find out self-efficacy of SMAN English teachers in using ICT, barriers they face, as well as the way they overcome the barriers. Using cluster random sampling, 20 teachers were taken as the sample. The data were collected through questionnaire. The questionnaire was adapted from Bandura (1997) and Catarina player-koro (2012). The result of the data analysis showed that the self-efficacy of the teachers on using ICT in teaching and learning activities in SMAN Kuansing in general was at a high category level. The highest percentage (80%) in believe of the ability and knowledge possessed agreed this statement. And the highest percentage (95%) in ‘believe of the ability on the use of ICT in learning process’ strongly agreed this statement. But teachers still have problem on the use of ICT because of several factors: Such as fear of making mistake, feeling under pressure dealing with people, and teachers still lack of ICT ability. Furthermore, several recommendations were given such as finding out the factors contribute to their problem on the use of ICT, finding the best way to cope with their problem, and doing more teaching using ICT. In line with that, government should give more attention to facilities and infrastructure, to help teachers implement the established curriculum. and to be more relaxed to express their ideas through ICT.Key Words: ICT, Self-efficacy, Teacher